Soil Structural Quality and Relationships With Root Properties in Single and Integrated Farming Systems - Cavalieri-Polizeli, Karina Maria Vieira; Marcolino, Feliciano Canequetela; Tormena, Cássio Antonio; Keller, Thomas; Moraes, Anibal de (Frontiers in Environmental Science, 2022)
Single farming systems (SFS) such as monocultures may negatively affect soil structural quality. This study tested the hypothesis that integrated farming systems (IFS), i.e., the combination of cropping and forestry and/or livestock farming, improves soil structural quality, root development and soil organic carbon. An experimental area was set up in 2012 at the Canguiri experimental farm belonging to the Federal University of Paraná, Southern Brazil. The soils are predominantly Ferralsols. The experimental treatments representing different farming systems, organized in a random block design with three replicates, were: Forestry (F), Conventional Crop Production (C), Livestock (L), and integrated Crop-Forestry (CF), Crop-Livestock (CL), Livestock-Forestry (LF), and Crop-Livestock-Forestry (CLF). In situ measurements and sampling were carried out in the 0–0.3 m layer during summer 2019/20, and included soil penetration resistance (PR), soil structural quality based on visual evaluation of soil structure (SqVESS scores), root length (RL), root volume (RV) and soil organic carbon content (SOC). Soil structural quality, penetration resistance, root length and volume, and SOC varied between farming systems, but no significant differences were found between single (C, L, F) and integrated farming systems (CF, CL, LF, CLF). The single system Forestry (F) and the integrated systems including forestry (LF, CF, CLF) tended to have higher SqVESS scores, i.e. poorer soil structural quality, and higher PR, which we associate with the generally drier soil conditions that are due to higher soil water uptake and higher interception and reduce the frequency of wetting-drying cycles. Roots were concentrated in the shallow soil layer (0–0.1 m depth), and this was especially pronounced in the Crop (C) single farming system. Based on the measured values, our results suggest an acceptable soil structural quality in all farming systems. Our data revealed strong, significant relationships between soil structural quality, penetration resistance, root growth and SOC, demonstrating that improvements in soil structure results in lower soil penetration resistance, higher root volumes and higher SOC, and vice versa. Soil PR was positively correlated with SqVESS (R2 = 0.84), indicating that better soil structural quality resulted in lower soil mechanical resistance. This, in turn, increased root length and volume, which increases carbon input to soil and therefore increases SOC in the long run.